Reliability, Criterion and Concurrent Validity of the Farsi Translation of DIVA-5: A Semi-Structured Diagnostic Interview for Adults With ADHD. Issue 12 (October 2021) - Zamani, Lida; Shahrivar, Zahra; Alaghband-Rad, Javad; Sharifi, Vandad; Davoodi, Elham; Ansari, Shadi; Emari, Fatemeh; Wynchank, Dora; Kooij, J. J. Sandra; Asherson, Philip
Objectives: This study evaluated the psychometrics of the Farsi translation of diagnostic interview for attention-deficit hyperactivity disorder (ADHD) in adults (DIVA-5) based on DSM-5 criteria.Methods: Referrals to a psychiatric outpatient clinic ( N  = 120, 61.7% males, mean age 34.35 ± 9.84 years) presenting for an adult ADHD (AADHD) diagnosis, were evaluated using the structured clinical interviews for DSM-5 (SCID-5 & SCID-5-PD) and the DIVA-5. The participants completed Conner's Adult ADHD Rating Scale-Self Report-Screening Version (CAARS-S-SV).Results: According to the SCID-5 and DIVA-5 diagnoses, 55% and 38% of the participants had ADHD, respectively. Diagnostic agreement was 81.66% between DIVA-5/SCID-5 diagnoses, 80% between SCID-5/CAARS-S-SV, and 71.66% between DIVA-5/CAARS-S-SV. Test–retest and inter-rater reliability results for the DIVA-5 were good to excellent.Conclusion: Findings support the validity and reliability of the Farsi translation of DIVA-5 among the Farsi-speaking adult outpatient population.